Bioterrorism preparedness training and assessment exercises for local public health agencies - Dausey, David J.; Lurie, Nicole; Diamond, Alexis; Meade, Barbara; Molander, Roger C.; Ricci, Karen A.; Stoto, Michael A.; Wasserman, Jeffrey (RAND, 2005)
Since September 11, 2001, and the subsequent anthrax attacks, the use of tabletop exercises in public health for emergency preparedness assessment and emergency response training has increased significantly. The evidence base for these exercises, however, remains sparse and the quality of many of these exercises is poor due to insufficient beta testing. Most exercises focus on training and few provide public health agencies (PHAs) with tools to assess exercise performance. This narrow focus limits the ability of PHAs to use tabletop exercises as part of an overall continuous quality improvement effort. In 2003, the U.S. Department of Health and Human Services Office of the Assistant Secretary for Public Health Emergency Preparedness contracted the RAND Corporation to develop and beta test a suite of tabletop exercises that focus on the response of local PHAs (LPHAs) to outbreaks caused by bioterrorism in the first few hours to days of the response. RAND developed the tabletop exercises described in this manual as templates that LPHAs can customize and use to train public health workers in how to detect and response to bioterrorism events and to assess LPHAs' levels of preparedness over time. They were beta tested and refined in 13 LPHAs across the United States over 10 months.